Serum Liver enzymes activity and some minerals level in the polycystic ovary patients in Salah Al-Deen governorate - Ibtihal K. Mahdi; Saria Naji; Wasan Sarhan (Tikrit Journal of Pure Science)
Polycystic ovary syndrome (PCOS) represents a commonly encountered metabolic- endocrinopathy that affects young women all over the world. It is characterized by hyperandrogenism, infertility and menstrual irregularity; as well as by being heterogeneous. PCOS was found to be associated with diabetes, insulin resistance, obesity and metabolic syndrome in large number of patients.